Analyzing the Fatigue Behavior of the β-Type Ti-15Mo Biomedical Alloy After Surface Modification with Laser - Campanelli, Leonardo Contri (2024)
Modifying the surface of titanium alloys with a laser considerably increases the specific area, which has beneficial implications for the osseointegration process. In this study, Yb:YAG laser was used to modify the surface of the commercial β-type Ti-15Mo alloy. The process parameters used were based on a suitable osseointegration condition for this treatment. The effect of such modification on the fatigue performance of the alloy was analyzed. To assess the impact of surface modification on the alloy’s fatigue performance, axial fatigue tests were conducted on specimens with both polished and laser-modified surfaces (R = 0.1). Fatigue strength was evaluated using a staircase method, where specimens were subjected to varying maximum stress levels to determine the fatigue limit after 5x106 cycles. The results showed that the laser-modified surface presented cavities and roughness values such that the effect on fatigue was highly detrimental. A reduction of around 75% in the fatigue limit (maximum stress) was obtained, indicating that modifying the Ti-15Mo alloy with laser for medical purposes may require integrated biological-mechanical development.